Body image disturbance, interoceptive sensibility and the body schema across female adulthood: a pre-registered study - Naraindas, Akansha M.; Cooney, Sarah M. (Frontiers in Psychology, 2023)
Introduction: Body image disturbance (BID) typically involves explicit negative attitudes toward one's shape and weight and is associated with altered interoceptive sensibility (the subjective perception of internal bodily states). This association is a known risk factor for the development and maintenance of eating disorders. However, while research has centred on younger women with eating disorders, diverse facets of BID appear in women without eating disorders across adulthood. Research shows that in the general population, young women (ages 18-25) with high BID exhibit disturbances in the body schema: an implicit sensorimotor representation of the body in space which includes mental simulation of a movement such as motor imagery. Given that body image is subject to age-related influences, it is important to investigate how age-related variation in BID can influence the body schema beyond young adulthood alone. Here, we examine the relationship between BID, interoceptive sensibility and the body schema across female adulthood. Methods: Cross-sectional data was collected online from 1214 women across four age groups: Young adults (18-24), Adults (25-39), Middle-aged adults (40-59), and Older aged adults (60-75). BID was indexed by questionnaires measuring body objectification, state, and trait body dissatisfaction. Interoceptive sensibility (IS) was measured using the MAIA-2 questionnaire. The body schema was evaluated through the Own Body Transformation task: a mental rotation task which assesses the capacity to make an embodied mental transformation. Results: Analyses revealed that while body objectification and trait body dissatisfaction decreased from young to older adulthood, state body dissatisfaction showed a marked increase. A negative relationship between IS and BID across all age groups was also evidenced. Finally, age, BID and orientation of the presented body were significant predictors of the time taken to make an embodied transformation. Discussion: These findings highlight the consistent relationship of BID and IS across age groups beyond young adulthood and demonstrate the varying importance of different aspects of BID as individuals age. We also evidence for the first time that disruptions in body image have the potential to impact implicit sensorimotor representations of the body even in women without eating disorders across female adulthood.